2018
DOI: 10.2217/fvl-2017-0146
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Receptors Drive Dengue Virus Immune Activation and Disease

Abstract: Dengue is a worldwide disease with 400 million annual infections that can lead to septic shock and viral hemorrhagic fever with internal bleeding. These symptoms are the result of uncontrolled immune activation. Macrophages and dendritic cells are the main target of dengue virus (DENV) and the cellular source of cytokines associated with this immune activation. Macrophages and dendritic cells express several innate immune receptors that have been implicated in DENV immune activation, of which, CLEC5A, RIG-I an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 136 publications
(236 reference statements)
0
22
0
5
Order By: Relevance
“…It has also been reported that POSTN recruits M2 tumor-associated macrophages and promotes glioma stem cells (GSCs) growth (30). CLEC5A is a spleen tyrosine kinase-coupled receptor, which is abundantly expressed in monocytes, macrophages and neutrophils, and critical for inflammation response (31, 32). A recent study has shown that CLEC5A is upregulated in GBM significantly and is associated with poor prognosis (33).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that POSTN recruits M2 tumor-associated macrophages and promotes glioma stem cells (GSCs) growth (30). CLEC5A is a spleen tyrosine kinase-coupled receptor, which is abundantly expressed in monocytes, macrophages and neutrophils, and critical for inflammation response (31, 32). A recent study has shown that CLEC5A is upregulated in GBM significantly and is associated with poor prognosis (33).…”
Section: Discussionmentioning
confidence: 99%
“…Their themes are summarized initially, followed by excerpts from specific cited references. Antibody-Dependent Enhancement (where enhanced virus entry and replication in a number of cell types is enabled by antibodies) [ [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] ]; Intrinsic Antibody-Dependent Enhancement (where non-neutralizing antibodies raised by natural infection with one virus may enhance infection with a different virus) [ [55] , [56] , [57] , [58] , [59] , [60] , [61] ]; Immune Enhancement (enhancement of secondary infections via immune interactions) [ [62] , [63] , [64] , [65] ]; Cross-reactivity (an antibody raised against one specific antigen has a competing high affinity toward a different antigen.) [ 66 , 67 ] Cross-Infection Enhancement (infection enhancement of one virus by antibodies from another virus) [ 68 , 69 ] Vaccine-associated Virus Interference (where vaccinated individuals may be at increased risk for other respiratory viruses because they do not receive the non-specific immunity associated with natural infection) [ [70] , [71] , [72] , [73] , [74] , [75] ]; Vaccine-Associated Imprinting Reduction (where vaccinations could also reduce the benefits of ‘imprinting’, a protection conferred upon children who experienced infection at an early age) [ 76 , 77 ]; Non-Specific Vaccine Effects on Immune System (where previous infections can alter an individual's susceptibility to unrelated diseases) [ 78 , 79 ]; Impact of Infection Route on Immune System (where immune protection can be influenced by the route of exposure/delivery) [ [80] , [8...…”
Section: Resultsmentioning
confidence: 99%
“…Viral infection triggers the activation of innate immunity pathways and leads to the transcription of genes responsible for antiviral responses in mosquitoes [60][61][62]. Innate immunity is a functional response against foreign organisms, formed in the long-term evolution process of mosquitoes after frequent viral infection, including RNA interference pathways, JAK-STAT, Toll and Imd pathways [63,64].…”
Section: Discussionmentioning
confidence: 99%